Assessing the Accuracy of Dermoscopy for Scabies Diagnosis in Dark African Skin - Nkechi Anne Enechukwu; Ikenna Akuakolam; Iloduba N Aghanya; Chetanna C Anaje; Ogochukwu I Ezejiofor; Enzo Errichetti (Dermatology Practical & Conceptual)
Introduction: Scabies, a parasitic infestation caused by Sarcoptes scabiei var hominis affects individuals of diverse skin types. While definitive diagnosis involves identifying adult mites, eggs, or scybala from the microscopy of scrapings obtained from representative sites; it is invasive, time-consuming and not feasible in very young or non-cooperating patients. Dermoscopy is an evolving non-invasive procedure useful in dermatological diagnosis. The handheld dermatoscope is portable and valuable for epidemics and in-vivo use. There is sparse data on the diagnostic accuracy of dermoscopy against microscopy in darker skin phototypes, a demographic for which dermoscopy have been understudied.